Artificial Intelligence in Education Building Technology Rich Learning Contexts That Work - Luckin, Rosemary (IOS Press, 2013)
The 13th International Conference on Artificial Intelligence in Education (AIED-2007) is being held July 9–13, 2007, in Los Angeles, California. AIED Conferences are organized by the International AIED Society on a biennial basis